Complete convergence of randomly weighted END sequences and its application - Penghua Li; Xiaoqin Li; Kehan Wu (Journal of Inequalities and Applications, 2017)
Abstract We investigate the complete convergence of partial sums of randomly weighted extended negatively dependent (END) random variables. Some results of complete moment convergence, complete convergence and the strong law of large numbers for this dependent structure are obtained. As an application, we study the convergence of the state observers of linear-time-invariant systems. Our results extend the corresponding earlier ones.